Prevalence of pregnancy anxiety and associated factors - Girija Kalayil Madhavanprabhakaran; Melba Sheila D'Souza; Karkada Subrahmanya Nairy (Elsevier, 2015)
Objective: To determine the prevalence of pregnancy-specific anxiety (PSA) and its associated factors among pregnant women during the three trimesters of pregnancy. Design: A prospective explorative survey was conducted among 500 low-risk Indian pregnant women of age 18-35 years. Setting: A major maternity government hospital in southern state of Kerala, India. Participants: 500 low risk pregnant women who attended the major maternity government hospital during the period June 2004-July 2005 were selected as convenient sample. Methods: An exploratory research design with a prospective cohort approach was adopted for the study. State Trait Anxiety Inventory (STAI) and Pregnancy-Specific Anxiety Inventory (PSAI) were used to collect the data. Results: Highest prevalence of pregnancy-specific anxiety (PSA) was reported during the third trimester of pregnancy. All pregnant women rated high levels of third trimester childbirth anxiety compared to other three components of pregnancy-specific anxiety. Nulliparous pregnant women reported higher levels of PSA than parous pregnant women (M = 134.40, M = 116.8). Young age, nulliparous status and nuclear family nature were identified as common risk factors of pregnancy-specific anxiety. Conclusion: During the transition to motherhood, the risk factors and timing of heightened pregnancy-specific anxiety differ. Higher prevalence of pregnancy anxiety among nulliparous and younger pregnant women necessitates an integrated routine screening of PSA during prenatal care. Early detection, prevention and management of pregnancy anxiety will enable women to cope with the challenges of pregnancy.